2010
DOI: 10.1093/ndt/gfq369
|View full text |Cite
|
Sign up to set email alerts
|

Skin autofluorescence is associated with renal function and cardiovascular diseases in pre-dialysis chronic kidney disease patients

Abstract: Tissue AGE accumulation measured as skin autofluorescence increased as GFR decreased and was related to CVD history in CKD patients. Non-invasive autofluorescence readers may provide potential markers for clinical risk assessment in pre-dialysis CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 31 publications
8
35
2
1
Order By: Relevance
“…Our observations confirm previous observations in a relatively small cohort of hospital-based Japanese patients that chronological age, diabetes, eGFR, and past history of CVE are independent determinants of SAF in participants with CKD stage 3 (29). In addition, we found that hemoglobin (negative association), past history of smoking, proteinuria, and social deprivation were also determinants of SAF in CKD stage 3.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our observations confirm previous observations in a relatively small cohort of hospital-based Japanese patients that chronological age, diabetes, eGFR, and past history of CVE are independent determinants of SAF in participants with CKD stage 3 (29). In addition, we found that hemoglobin (negative association), past history of smoking, proteinuria, and social deprivation were also determinants of SAF in CKD stage 3.…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes has been shown to be an independent determinant of higher SAF values in participants with and without CKD (3,22,29). We observed significantly higher SAF readings in those with diabetes compared with those without (Table 4), and confirmed diabetes as an important independent determinant of SAF in the multivariable analysis ( Table 5).…”
Section: Diabetes As a Determinant Of Higher Safsupporting
confidence: 75%
See 3 more Smart Citations